Educational inequalities related to gender and migrant background at the transition to Higher Education. Findings from Switzerland, Germany and France - Griga, Dorit; Hadjar, Andreas (Swiss Journal of Educational Research, 2018)
The paper deals with the transition to Higher Education focusing on educational inequalities at the intersection of gender and migrant background. At the core of the analyses, theorized referring to decision theory, is a comparison of Switzerland (TREE), Germany (HIS-Studienberechtigte 2002) and France (Panel d’élèves du second degré 1995). Results indicate increased transition rates to Higher Education for second-generation males from some socially disadvantaged migrant groups for Switzerland and Germany, if controlled for social origin. Evidence confirming a female disadvantage for second generation females originating from countries characterised by a rather patriarchal culture were not found in any of the countries under consideration.